Obligation to Pay Online Loans: Dissecting the Principles of Debt Legality in the Digital World - Pransisto, Johamran; Sitinjak, Humala; Sitinjak, Imman Yusuf; Junaidi, Junaidi; Thio, Ricky; Rohani, Aceng Asnawi (Faculty of Law, Universitas Pekalongan, 2024)
Examining the duty to repay online loans within the framework of debt legality in the digital age, and how successful monitoring and enforcement of laws have been in enforcing online loan rules in Indonesia are the overarching goals of this study. Findings are based on logical viewpoints, critical analysis, and philosophy; the study takes a normative legal stance with analytical descriptive methodologies; it examines pertinent laws and regulations as well as applicable law enforcement activities. In particular, when it comes to dealing with unregistered fintech, the findings reveal a disconnect between current legislation and the efficacy of its oversight. Issues with implementation and enforcement of legislation continue to affect consumer protection and transaction fairness, despite efforts to promote transparency and consumer protection via regulations like Financial Services Authority Regulation Number 77/POJK.01/2016. For better management, this study suggests tightening the regulatory framework and boosting inter-institutional cooperation.